Metal Organic Framework as an Adsorbent for Desulphurization - Xueqin Zhao; Chunling Xin; Yanchao Yin; Xiaoguang Tian; Yongchao Li; Wanying Bian; Piyong Lian (Adsorption Science & Technology)
In this study, a metal organic framework (MOF-14) was successfully synthesized under hydrothermal conditions and applied in deep desulphurization. In this article, as-synthesized MOF-14 samples were characterized by powder X-ray diffraction, thermogravimetric analysis and microscopic photography. The desulphurization effect of MOF-14 was quantified by adsorbing organosulphur compounds, such as thiophene, benzothiophene, dibenzothiophene and 4,6-dimethyldibenzothiophene from model petrol. The experimental result revealed that MOF-14 is an excellent adsorbent in removing organosulphur compounds from model petrol. In addition, it was proved that MOF-14 is highly selective towards the removal of organosulphur compounds from aromatic model petrol. Regeneration experiments show the reversible nature of the adsorbent.